An evaluation of the cooperative learning process by sixth-grade students. (May 2016) - Genç, Murat
The purpose of this study is to investigate the effectiveness of cooperative learning on the science lessons achievement of primary school students and to designate their views on cooperative learning process. 135 sixth-grade students attending the same school took part in the study. The model of this study was the Solomon four-group model. In the study, the Cooperative Learning Process Scale and the Science Achievement Test were used to collect data. In the light of the findings, the cooperative learning activities done in the experimental group have meaningfully increased the student achievement in comparison to the control group. According to the findings, it was determined that the activities were prepared appropriately to the cooperative learning and that they were organised considering the basic principles of cooperative learning. 85.07 per cent of the students have stated that the activities done were appropriate for high level cooperative learning.